Dermatological manifestations relating to nutritional deficiencies after bariatric surgery: case report and integrative literature review - Andressa Christine Ferreira Silva,; Kazmarek, Laura Moya; Souza, Elemir Macedo de; Cintra, Maria Letícia; Teixeira, Fernanda (São Paulo Medical Journal, 2022)
BACKGROUND: The number of bariatric surgeries performed worldwide is growing. Among the main short, medium or long-term complications after surgery are nutritional deficiencies. Many of these, such as those of Zn, Cu and vitamins A, B1, B3, B6 and B12, are manifested by dermatological lesions before potentially fatal systemic disorders occur. OBJECTIVE: To identify the main dermatological manifestations associated with nutritional deficiencies after bariatric surgery, and the associated variables. DESIGN AND SETTING: Integrative literature review carried out at a public university in Brazil. METHODS: This was a case report and a review of health research portals and databases of national and international biomedical journals, without publication date limitation. The descriptors used for searches followed the ideal methodology for each database/search portal: “bariatric surgery”, “skin”, “skin disease”, “skin manifestation”, “deficiency disease” and “malnutrition”. RESULTS: A total of 59 articles were selected, among which 23 were review articles or articles that addressed specific dermatological manifestations. The other 36 articles described 41 cases, which were organized into a table with the clinical variables. CONCLUSIONS: Although nutritional deficiencies are expected as complications after bariatric surgery, few articles relating them to their dermatological manifestations were found. It is important to recognize skin changes caused by nutritional deficiencies in patients treated via bariatric surgery, as these may occur before systemic complications appear and are easier to diagnose when the patient does not have any systemic symptoms yet. However, there is generally a delay between the appearance of skin lesions and making the diagnosis of nutritional deficiency.